2014
DOI: 10.5901/mjss.2014.v5n18p187
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing as an Organizational Phenomenon Impeding Implementation of Changes

Abstract: Most of organizations in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Of note is that over one-half (63%) of the respondents reported being bullied regularly or sporadically at some point during their working careers. This percentage is higher but still consistent with what is reported in other international nursing samples (Spector et al 2014;Vessey et al 2010) and somewhat less than reported in other Russian professions' labour studies (Safina & Podgornaya 2014). Characteristics of the prevailing culture including role expectations, behavioural intentions and actions influence the prevalence of bullying that occurs both in the schoolyard and the workplace (Bond 2004).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Of note is that over one-half (63%) of the respondents reported being bullied regularly or sporadically at some point during their working careers. This percentage is higher but still consistent with what is reported in other international nursing samples (Spector et al 2014;Vessey et al 2010) and somewhat less than reported in other Russian professions' labour studies (Safina & Podgornaya 2014). Characteristics of the prevailing culture including role expectations, behavioural intentions and actions influence the prevalence of bullying that occurs both in the schoolyard and the workplace (Bond 2004).…”
Section: Discussionsupporting
confidence: 81%
“…; Vessey et al. ) and somewhat less than reported in other Russian professions’ labour studies (Safina & Podgornaya ). Characteristics of the prevailing culture including role expectations, behavioural intentions and actions influence the prevalence of bullying that occurs both in the schoolyard and the workplace (Bond ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The mobber is "the executioner," the one who begins and performs the mobbing behaviors. The mobber has a persecutory intent; the victim is harassed, discriminated against, and treated differently from others because of a specific and coherent vexatious intent (Bartalucci, 2010;Ehe, 2010;Safina & Podgornaya, 2014). In their analysis of the phenomenon, Acquadro Maran, Bernardelli and Varetto (2018) found that mobbers could be categorized as follows:…”
Section: Actors In Mobbingmentioning
confidence: 99%
“…This does not employ any form of collective physical abuse of employees; but rather targeted largely on the victim's innermost self. This is why Safina and Podgornaya (2014) believe that mobbing can take such an emotional toll on its victims that it eventually results to physical health damage. The persistent pressure that mobbing provokes in targets make relaxation difficult at work or away from work and cause fatigue.…”
Section: Workplace Mobbingmentioning
confidence: 99%